Dynamic Effects of Energy Consumption on Economic Growth in an Emerging Economy - Sriyana, Jaka (International Journal of Energy Economics and Policy, 2019)
The main objective of this research is to investigate the dynamic effects of energy consumption on economic growth in the Indonesian context. Based on the annual data of 1990-2017, the empirical ARDL model presents significant effects of energy use, electric power and renewable energy consumption on economic growth. The analysis using error correction model presents the long-run effect of energy use on economic growth. In the short-run, the electric power consumption and labor participation rate have a positive effect on economic growth. The variable of energy use has symmetric effects both in long and short-term periods. The electric power and renewable energy consumption have asymmetric effects in the long-and short-run models. This paper highlights that energy consumption and labor force are the main sources of economic growth in this country. It implies that the research findings are in line with the neoclassical theory. Keywords: Economic Economic Growth, Energy Use, Renewable Energy JEL Classifications: O47, O13, O52 DOI: https://doi.org/10.32479/ijeep.7787